2005
DOI: 10.1002/jcp.20362
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived growth factor‐BB (PDGF‐BB) induces differentiation of bone marrow endothelial progenitor cell‐derived cell line TR‐BME2 into mural cells, and changes the phenotype

Abstract: Blood vessels are composed of endothelial cells (EC) and mural cells, and the interaction between EC and mural cells is essential for the development and maintenance of the vasculature. EC differentiate from bone marrow-derived endothelial progenitor cells (EPC). Recently, we established a conditionally immortalized bone marrow EPC-derived cell line, TR-BME2, and a brain capillary EC (BCEC) line, TR-BBB, from temperature-sensitive-SV40 T-antigen gene transgenic rats. To understand the function of EPC, it is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Recent reports indicate that vascular progenitor cells are able to differentiate into contractile-type SMCs in the absence of VEGF or into synthetictype SMCs in the presence of PDGF-BB, respectively (Miyata et al, 2005). However, reports have also shown that treatment of…”
Section: Discussionmentioning
confidence: 92%
“…Recent reports indicate that vascular progenitor cells are able to differentiate into contractile-type SMCs in the absence of VEGF or into synthetictype SMCs in the presence of PDGF-BB, respectively (Miyata et al, 2005). However, reports have also shown that treatment of…”
Section: Discussionmentioning
confidence: 92%
“…Platelet-derived growth factor-BB (PDGF-BB) has been identified as one of the key modulators for SMC differentiation from stem/progenitor cells (1,10,11) and mature vascular SMC phenotype modulation (12,13). Our previous experiments showed that SMC differentiation from ES cells was enhanced through short stimulations with PDGF-BB (within 24 h) in the absence of serum, indicating that the duration of serum deprivation and the proliferation stage of cells are important parameters in SMC differentiation mediated by PDGF-BB (7).…”
Section: Embryonic Stem (Es)mentioning
confidence: 99%
“…It was also observed that mesenchymal stem cells can differentiate into both ECs and SMCs 72 and that vascular progenitor cells are able to differentiate into contractile-type smooth muscles in the absence of VEGF or into synthetic-type phenotypes in the presence of PDGF-BB, respectively. 117 In addition, immune suppression drug cyclosporine can inhibit both endothelial and smooth muscle progenitor cell growth and thus influences neointimal formation in transplant models. 118 In human embryonic stem cells, a report demonstrated that a population of vascular progenitors with the ability to differentiate into endothelial-like and smooth muscle-like cells has been identified.…”
Section: A Common Progenitor For Endothelial and Smcsmentioning
confidence: 99%